English Days Program (EDP) as a Basis of Developing Students’ Foreign Language Awareness in STAIN Bukittinggi - Hayati Syafri (Proceedings of ISELT FBS Universitas Negeri Padang, 2014)
The background of the research is the lack of students’ foreign language awareness in STAIN Bukittinggi for improving their speaking ability. Students are nervous and anxiety to practice their English in the speaking class. So that, teacher created English Days Program (EDP). The purpose of the research is to get the information whether the activities in EDP can develop students’ language awareness in practicing their English. This research uses qualitative research. The population is the English students in STAIN Bukittinggi and the sample is the students in the second semester academic year 2014-2015. The data collection is the interview by the snowball sampling where the samples are studying speaking in this semester with the researcher as the pioneer of EDP. The result of the research is all informants agree that EDP can develop their English language awareness because they always get the motivation to do that. Besides, they are also helped by the EDPs’ systematic systems that control them. So, even though they faced many problems in speaking, they believed that EDP is still a good program to improve their language awareness in English.